2021
DOI: 10.3390/ijerph18116121
|View full text |Cite
|
Sign up to set email alerts
|

Home Environment and Early Development of Rural Children: Evidence from Guizhou Province in China

Abstract: Delays in early child development are among the aspects underlying the persistent developmental gaps between regions and social strata. This study seeks to examine the relationship between the home environment and early child development in less-developed rural areas by drawing on data from 445 children from villages in Guizhou province in southwest China. A demographic questionnaire, the Home Observation Measurement of the Environment (HOME), and the Bayley Scales of Infant Development, version III (BSID-III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous studies also suggested that young children who lack material environment stimulation in rural families will lead to inability to solve problems in social situations (Jeon et al, 2014), which is difficult for them to concentrate and completely remember the rules in getting along with others and restraining their negative emotions, resulting in a series of social communication problems and social withdrawal behavior (Valadi et al, 2020). The executive function problems caused by the lack of material environment stimulation in rural families may lead to children's inability to solve problems in social situations (Kuhn et al, 2021), which is difficult for them to concentrate and completely remember the rules in getting along with others and restraining their negative emotions, resulting in a series of social communication problems and social withdrawal behavior. This study further shows that in addition to EF, receptive language ability also partially mediates the impact of household chaos on social withdrawal behavior.…”
Section: The Mediating Role Of Ef and Receptive Language Abilitymentioning
confidence: 99%
“…Previous studies also suggested that young children who lack material environment stimulation in rural families will lead to inability to solve problems in social situations (Jeon et al, 2014), which is difficult for them to concentrate and completely remember the rules in getting along with others and restraining their negative emotions, resulting in a series of social communication problems and social withdrawal behavior (Valadi et al, 2020). The executive function problems caused by the lack of material environment stimulation in rural families may lead to children's inability to solve problems in social situations (Kuhn et al, 2021), which is difficult for them to concentrate and completely remember the rules in getting along with others and restraining their negative emotions, resulting in a series of social communication problems and social withdrawal behavior. This study further shows that in addition to EF, receptive language ability also partially mediates the impact of household chaos on social withdrawal behavior.…”
Section: The Mediating Role Of Ef and Receptive Language Abilitymentioning
confidence: 99%
“…The environment at home is crucial, and essential for the first months of infancy, due to the presence of stimuli for learning, responsive care, and organization in the home environment. Positive correlations were observed between parental practices, an adequate environment, and child development; infants and children aged 4 to 26 months succeeded in the domains of language, and in gross motor and socio-emotional development [ 24 ].…”
Section: Introductionmentioning
confidence: 99%